Kepemimpinan Transformasional dalam Pelayanan e-Procurement (Studi di Unit Pengelola Pengadaan Barang dan Jasa Universitas Timor) - Payon, Filogus Naboyut (Badan Penerbitan Jurnal (BPJ) FIA-UB, 2021)
Leaders roles in building working environment are vital. Therefore, transformational leadership required motivation and performances. This research aimed to investigate role of transformational leadership in e-Procurement at the Goods and Services Procurement Management Unit at the University of Timor. How transformational leadership and what factors obstruct and support in e-Procurement implementations. This research uses descriptive-qualitative approach to obtain comprehensive overview. The result shows that principal implementations in goods/ services and transformational leadership roles in e-Procurement has been implemented. Lack of human resources, low management competence in procurement and unclear career developments impact administrators on how serious they are. Nevertheless, Head of UPPBJ at University of Timor has high commitment becomes great power to reach the vision, mission and goals. Also, the existence of procurement agent can direct, guide and offer solutions to any obstacles faced by UPPBJ at University of Timor.